Exploring new Dive Tourist Cohorts on the Great Barrier Reef - Cummins, Terrence; Pabel, Anja; Prideaux, Bruce R. (Tourism in marine environments, 2023)
This research note reports on previously undescribed cohorts of dive tourists and contributes to the current body of knowledge about dive tourist segments. Findings are based on conversations with 138 passengers who volunteered comments whilst returning from the Great Barrier Reef Marine Park (GBRMP) on commercial day-trip and liveaboard (overnight) vessels. The study identified six new dive tourist cohorts. The findings highlight the importance that travel companions play in the decision-making of dive tourists with implications for customer value creation. The findings also may indicate an emerging trend in the adventure tourism market where participants are unlikely to become dedicated enthusiasts in adventure activities such as scuba diving. These insights also have implications for the dive tourism industry as a potential way to increase dive tourist numbers.